PELATIHAN STRATEGI MENCARI DAN MELAMAR PEKERJAAN DI ERA PANDEMI COVID-19 KEPADA ALUMNI PERGURUAN TINGGI - Saiful Rahman Yuniarto; Gunawan Eko Nurtjahjono; Raden Rustam Hidayat; Edy Yulianto; Muhammad Faisal Riza (Dharma: Jurnal Pengabdian Masyarakat, 2021)
The high unemployment rate is a fundamental problem in employment in our country, where the new workforce that is added is far greater than the increase in employment. Unemployment is a problem for countries with high population growth rates, and unemployment can also affect the level of the economy. At the beginning of 2020, world economic growth experienced a decline due to the coronavirus disease outbreak, this coronavirus (covid-19) had an impact on economic growth in the form of a decline in the level of the world economy, including Indonesia. Seeing conditions like this, special attention is needed for alumni to prepare students for the world of work. This community service is carried out in the form of training on strategies for finding and applying for jobs, the problem solving framework provided is by providing training so that it can increase knowledge and insight to job seekers college alumni about srategies for finding and applying for jobs.The purpose of this community service activity is to provide training to college alumni so that they have the readiness to find and apply for jobs. This community service activity is carried out virtually online online in the form of training and guidance. The target is college alumni who will definitely be involved in the activity of finding and applying for jobs, at the initial stage the presenter will deliver a theoretical presentation accompanied by realistic examples. The results of the implementation of community service by providing the training are expected that college alumni as prospective job seekers already have the knowledge, insight and readiness in finding and applying for jobs, then to provide knowledge and insight about strategies for finding and applying for these jobs, as well as the factors that must be considered.The high unemployment rate is a fundamental problem in employment in our country, where the new workforce that is added is far greater than the increase in employment. Unemployment is a problem for countries with high population growth rates, and unemployment can also affect the level of the economy. At the beginning of 2020, world economic growth experienced a decline due to the coronavirus disease outbreak, this coronavirus (covid-19) had an impact on economic growth in the form of a decline in the level of the world economy, including Indonesia. Seeing conditions like this, special attention is needed for alumni to prepare students for the world of work. This community service is carried out in the form of training on strategies for finding and applying for jobs, the problem solving framework provided is by providing training so that it can increase knowledge and insight to job seekers college alumni about srategies for finding and applying for jobs.The purpose of this community service activity is to provide training to college alumni so that they have the readiness to find and apply for jobs.This community service activity is carried out virtually online online in the form of training and guidance. The target is college alumni who will definitely be involved in the activity of finding and applying for jobs, at the initial stage the presenter will deliver a theoretical presentation accompanied by realistic examples. The results of the implementation of community service by providing the training are expected that college alumni as prospective job seekers already have the knowledge, insight and readiness in finding and applying for jobs, then to provide knowledge and insight about strategies for finding and applying for these jobs, as well as the factors that must be considered.